We Reddit in a Forum: The Influence of Message Boards on Firm Stability - Corbet, S.; Hou, Y.; Hu, Y.; Oxley, Leslie (2022)
The use of messaging boards to instigate coordinated manipulation of stock prices is not a novel phenomenon. However, the growing breadth and sophistication of social media, the widespread availability of technological cloaking techniques, and the ready accessibility of leveraged derivatives have all significantly contributed to the growth of the infamous Reddit forum r/wallstreetbets. Using a lexicon of terminology designed to identify explicit and implicit manipulation attempts, this research presents several novel findings. The results indicate significantly positive, pronounced, and persistent abnormal returns in the aftermath of manipulative events, with the results being robust across several testing procedures. These abnormal returns have increased significantly in line with the growth of forum users and the reach of manipulation-related comments. Significant effects on market liquidity and analyst recommendations are further identified across tests. Such continued predatory headwinds are certainly of interest to market-makers, regulators, and policymakers alike, as the irrational exuberance incited by millennial meme stocks and sarcastic GIFs is found to have played a significant role in disrupting market functionality. The desired outcome of some of these five million monthly forum users is to create enough momentum to trigger algorithmic responses to move out-of-the-money options into a profitable state. Our results present evidence that this potential threat to corporate stability is concrete.